Why Do Relatively Few Economists Work on Climate Change? A Survey - Nico Pestel; Andrew J. Oswald (Institute of Labor Economics (IZA), 2021)
Climate change is sometimes viewed as the most serious problem facing modern society. The science behind anthropogenic global warming has been understood for more than half a century. Yet relatively few economists work on topics related to climate change. What explains this (apparent) lack of interest from economists? Here we report the results of a survey to try to understand economists' views and actions. More than 90% of respondents state that they are concerned about climate change. Our survey then asks the respondents why they have not done research on the topic. The most frequent response (given by approximately 80% of economists) is that they do not feel they have enough time and resources to be able to work on climate change. We discuss possible explanations and concerns.
Keywords: A11; Q54; 330; climate change; economics